Recent evolution of renal replacement therapy in the critically ill patient - Ronco, Claudio (BioMed Central, 2006)
The epidemiology of severe acute renal failure has dramatically changed in the past decade. Its leading cause is sepsis and the syndrome develops mostly in the intensive care unit as part of multiple organ dysfunction syndrome. After the significant improvements obtained from the mid 1970s to the mid 1990s, the past decade has seen a dramatic evolution in technology leading to new machines and new techniques for renal and multiple organ support. Extracorporeal therapies are now performed using adequate treatment doses, which have resulted in improved survival in the general population. At the same time, patients with sepsis seem to benefit from the use of increased doses, as in the case of high-volume hemofiltration or of increased membrane permeability and sorbents as in the case of continuous plasmafiltration adsorption. The humoral theory of sepsis and the peak concentration hypothesis have spurred a significant interest in the use of such extracorporeal therapies for renal support and possibly for the therapy of sepsis. Ongoing research and prospective studies will further elucidate the role of such therapies in this setting.